Gender influence on ICT use by undergraduates in two university libraries in Nigeria (2013)
ICT use helps to facilitate easy access to electronic information for research and learning purposes by undergraduates. The objective of this study was to investigate the influence of gender on the use of ICT among undergraduates in two university libraries in Nigeria. Undergraduates from three faculties were randomly selected to give a sample of 223, which is 30% fraction of the total population of 12,353. Questionnaire was the data collection method used. The undergraduates used ICT for research purpose and to support course of study. ICT use was higher among the undergraduates in Lead City University than those in University of Ibadan. ICT use was influenced by gender in both universities. Recommendations based on the outcome of this study were highlighted in this paper.